PENGARUH KONSEP DIRI TERHADAP MOTIVASI BELAJAR PADA MATA PELAJARAN IPS SMA NEGERI 7 MERANGIN - Sundra, Rike; Elvina Safitri (Jurnal Ilmu Manajemen Terapan, 2020)
This research is motivated by the low self-concept of students which is characterized by a lack of student confidence in themselves and low motivation to learn in students. The purpose of this study was to determine the effect of self-concept on student learning motivation in social studies. The research method used is quantitative with simple linear regression analysis techniques. The research respondents were 50 high school students of SMA Negeri 7 Merangin. Data collection by researchers is done by questionnaire or questionnaire. Trials on the research instrument of the researcher are validity and reliability testing. The test for classical assumptions using the normality test and Linearity test with the help of SPPS application 20. The results showed that students' self-concepts have a significant influence on student motivation which is shown in the regression coefficient of 0.728 and the R Square coefficient of 0.403 is terminated.